2020
DOI: 10.1016/j.aimed.2020.07.011
|View full text |Cite
|
Sign up to set email alerts
|

The effects of vitamin D on acute viral respiratory infections: A rapid review

Abstract: Brief overview Current evidence suggests vitamin D replacement may reduce risk for acute respiratory tract infections (ARTI) in people with deficiency or insufficiency, although the effects of supplementation on incidence and severity of ARTI in the general population remain unknown. Oral vitamin D supplemzentation taken at routine doses appears to be generally safe and well tolerated. Verdict Current experimental evidence remains inconclusive regarding the effects of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 32 publications
0
18
0
1
Order By: Relevance
“…Indeed, a recent review has shown the importance of maintaining a correct nutritional status of 10 nutrients analyzed for the health of the immune system, highlighting especially the importance of Vitamin D and iron in the context of COVID-19 [39][40][41]. A wealth of mechanistic and clinical data has shown that vitamins, including vitamins A, B 6 , B 12 , C, D, E, and folate; trace elements, including zinc, iron, selenium, magnesium, and copper; and the omega-3 fatty acids eicosapentaenoic acid and docosahexaenoic acid play important and complementary roles in supporting the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent review has shown the importance of maintaining a correct nutritional status of 10 nutrients analyzed for the health of the immune system, highlighting especially the importance of Vitamin D and iron in the context of COVID-19 [39][40][41]. A wealth of mechanistic and clinical data has shown that vitamins, including vitamins A, B 6 , B 12 , C, D, E, and folate; trace elements, including zinc, iron, selenium, magnesium, and copper; and the omega-3 fatty acids eicosapentaenoic acid and docosahexaenoic acid play important and complementary roles in supporting the immune system.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 98 , 99 , 100 Nutritional deficiencies can impair immune function and increase the risk for a more severe and chronic course of disease. 30 , 47 , 48 , 49 , 50 , 51 , 101 Malnutrition has been noted in 26-45% of patients with COVID-19. 5 A study on 50 hospitalized patients with SARS-CoV-2 revealed 76% were vitamin D deficient and 42% selenium deficient.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C deficiency results in impaired immunity, leading to increased rates and severity of infection such as pneumonia, whereas supplementation can reduce the incidence and severity of infection [5,42e44]. A recent review concluded that vitamin C supplementation may reduce symptoms of acute respiratory viral infections, as well as the incidence and duration of hospital stays [43]. Daily vitamin C supplementation at 200 mg or more, was reported to decrease severity and duration (8% in adults, 14e18% in children) of upper respiratory tract infections, including common cold [45].…”
Section: Vitamin Cmentioning
confidence: 99%